PENGARUH JUMLAH TENAGA KERJA, TINGKAT PENDIDIKAN DAN JUMLAH PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI KABUPATEN MAGELANG TAHUN 1996-2017 - Heni Wahyu Widayati; Lorentino Togar Laut; Rian Destiningsih (DINAMIC : Directory Journal of Economic, 2019)
Economic growth is one measure in determining people's welfare. One of the economic problems that occur in Magelang Regency is unemployment. The number of unemployed people in Magelang Regency  still  cannot  be  reduced,  this  brings  various  challenges  for  local  governments  in overcoming the number of unemployed. The purpose of this study is to find out the effect of the number of workers, education level and number of unemployed on economic growth in Magelang Regency in  1996-2017.  The data  analysis  method  that  the researcher  used  in  this  study  was multiple linear regression analysis with OLS (Ordinary Least Square) model. The collected data is secondary data, the technique of collecting data uses document studies obtained from the Central Statistics Agency (BPS) in the period 1996-2017. The variable number of labor has a significant effect on the economic growth of Magelang Regency in 1996-2017. While the education level variable and the number of unemployed did not significantly influence the economic growth of Magelang Regency in 1996-2017. In this study the results obtained that the overall independent variables  consisting  of  the  number  of  workers,  education  level  and  number  of  unemployed simultaneously have a significant effect on the value of economic growth in Magelang Regency in 1996-2017.